At a glance histologi / Michelle Peckham ; alih bahasa Juwalita Sarapsari ; editor, Sally Carolina, Rina Astikawati - PECKHAM, Michelle; Juwalita Sarapsari; Sally Carolina; Rina Astikawati (Erlangga, 2014)
108 hlm. : ilus. ; 28 cm.